SYSTEMIC POLICY AS CRIMINAL POLITICS IN ERADICATING CORRUPTION IN INDONESIA - WP. Djatmiko (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
Criminal Policy is a rational organization of the control of crime by society, which can be carried out operationally through a penal or non-penal policy. Reality shows that there is a flaw in penal policy in preventing crime act of corruption in Indonesia. Various efforts have been done to eradicate corruption, starting from law enforcement, political will, legislative policy, establishment of special institutions/commissions, improvement and reformation on bureaucracy, law socialization in various circles, and establishment of international cooperation. Yet, all of those efforts have not yielded maximum results. In Indonesia, corruption is still raging. Therefore, the corruption prevention policy should rely on not only penal policy, but also non-penal policy (systemic policy). The corruption prevention policy using systemic approach is a strategic policy as it is more preventive in dealing with corruption. The main goal of systemic policy is to handle and reduce the causative factors of criminal act of corruption.